Pendidikan Seks Bagi Anak Tunagrahita Di SLB Purnama Asih - Sabrina Mufidatul Ummah; Dinda Nur Akmalia; Arra Syafa Maura; Kesya Adelia Avianika; Siti Hamidah (Jurnal Bintang Pendidikan Indonesia, 2023)
Based on data SIMFONI PPA, throughout 2021 there were 987 cases of violence against children with disabilities experienced by 264 boys and 764 girls. The same data reveals that the type of violence with the highest number of victims is sexual violence, namely 591 victims. From this data it is possible that there will be an even higher increase. Therefore, children with special needs need special guidance and direction in understanding their physical and psychological changes as well as prevention and knowledge about the importance of gender identity and sexuality. Teaching sex is very important, especially for children with special needs in order to prevent sexual harassment. Through the media of songs teaching sex can be done effectively, especially for children. 54% of the achievements in this research were well achieved. Perhaps the remaining 46% will be a further task for researchers, teachers or other parties who wish to develop this research in a more innovative way.